One health and human animal-bond intervention strategies- assessing veterinary-social service collaborations - Orchard, Ronald J.; Scarbrough, Elizabeth; Crow, Allison; Baldwin, Matt; Moreau, Cassidy (Frontiers in Veterinary Science, 2026)
This study evaluates a novel interdisciplinary outreach model integrating veterinary care, social work, and public health services to serve unhoused populations and their companion animals in Topeka, Kansas. Grounded in structural vulnerability theory and One Health principles, the project examined the Street Dog Coalition’s (SDC) partnership with the Mobile Access Partnership (MAP), focusing on how the human-animal bond functions as a catalyst for trust, engagement, and care continuity. Using a qualitatively driven, mixed-methods design, the research team conducted 12 semi-structured interviews with beneficiaries, volunteers, program staff, and external collaborators, supplemented by descriptive service utilization data. Thematic analysis revealed six interrelated themes: the transformative power of the human-animal bond, trust-building as foundational to engagement, structural barriers to care continuity, tensions in the graduation process, emotional impact on providers, and the emergence of a relational ecosystem of care. Findings underscore the relational and structural dynamics of service delivery, highlighting the dual importance of compassionate, trauma-informed care and policy-level reforms. This research contributes to the growing evidence base for integrated One Health interventions and offers critical insight into how veterinary-social service collaborations can operationalize equity, dignity, and mutual healing in structurally vulnerable contexts.